Peers, Predators, and Porn: Predicting Parental Underestimation of Children's Risky Online Experiences. Issue 2 (1st January 2014) - Byrne, Sahara; Katz, Sherri Jean; Lee, Theodore; Linz, Daniel; McIlrath, Mary
Abstract: Parents often underestimate the degree to which their children engage in risky online activities such as cyberbullying, worrisome interactions with strangers, and exposure to sexual content. This study attempts to identify the underlying predictors of such parental misconceptions. A national sample survey (nonrandom) of 456 matched parent–child pairs revealed that a permissive parenting style, difficulty communicating about online risks, and household environmental variables such as having access to a private computing space play a role in parental underestimation of risky social interactions that their children encounter and experience online. Implications for scholars and caregivers are discussed.